“SEGO KUCING” MBOK MISNATI UPAYA MEMBANGUN KETAHANAN PANGAN NASIONAL MELALUI REVITALISASI NILAI KEARIFAN LOKAL - Purnomo, Hari (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
Sego Kucing Mbok Misnati contributes positively to the development of the local economy through the culinary tourism sector in Banyuwangi. The success of Sego Kucing Mbok Misnati in maintaining its authenticity and traditional taste has attracted not only local tourists but also international tourists. The presence of Sego Kucing Mbok Misnati has had a significant economic impact on the parties involved. The production activities of Sego Kucing carried out by Mbok Misnati have become the center of economic activities involving various parties, such as local farmers, local traders, and the workforce involved in the production process. Sego Kucing Mbok Misnati can be an inspiration for other local culinary entrepreneurs. Sego Kucing Mbok Misnati is not only delicious and culturally valuable food but also a symbol of success in building the economy and food security through culinary tourism, as well as preserving and appreciating local wisdom that is part of the regional cultural identity. This study aims to investigate the role of Sego Kucing Mbok Misnati in building national food security through the revitalization of local wisdom values. The research method used is qualitative, using primary data obtained through interviews with Mbok Misnati as the owner of Sego Kucing stall, as well as direct observation of the production and consumption process of Sego Kucing. Secondary data was obtained from relevant literature studies. The results of the study show that Sego Kucing Mbok Misnati plays an important role in building national food security through the revitalization of local wisdom values, in addition to being a typical cuisine of Banyuwangi. Sego Kucing, which has become a world cultural heritage, can be one of the region's flagship products and increase the income of the local community. The revitalization of local wisdom values has been carried out through the preservation of recipes, traditional cooking techniques, and the use of high-quality local ingredients.